CARBON EMISSION DISCLOSURE UNDER CEO POWER: THE CONTINGENT ROLE OF FIRM VALUE - Krisyadi, Robby; Elaine; Ramadana, Mariska; Hesniati (JRAK, 2026)
Climate concerns have heightened the importance of transparent carbon disclosure; however, leadership power may hinder such practices. This study aims at examining the effect of CEO power on Carbon emission disclosure (CED), with firm value as a moderating variable, among 87 firms listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023, using panel regression and interaction models in Stata. The results indicate that CEO power significantly reduces CED, and firm value positively moderates this negative relationship. This suggests that in firms with higher market value, CEOs wield greater influence and face weaker monitoring pressures, thereby enabling them to limit disclosure. The findings support stakeholder and upper echelons' perspectives by highlighting the constraining role of powerful CEOs in corporate transparency efforts. Practically, the study underscores the importance of strengthening governance mechanisms in high-value firms to ensure that increasing market valuation does not amplify managerial discretion that weakens carbon disclosure.